PRODUCT PLACEMENT IN THE FILM ADA APA DENGAN CINTA - Santika, Amelia Putri; Rosmiati, Ana (Seni Media Rekam ISI Surakarta, 2020)
Nowdays film is not only a medium of entertainment, but also a medium for product promotion or as a medium for advertising products or public service advertisements. This function can be found in the film Ada Apa Dengan Cinta 2. The purpose of this study is to analyze the characteristic of the product advertisement inserted in the film Ada Apa dengan Cinta 2. The type of research used is Descriptive Qualitative. Data collection techniques using Purposive Sampling to obtain three research samples, namely Aqua, Loreal, and Line. Data analysis was done by Interpretative Video-Analysis. The results showed that in the film Ada Apa dengan Cinta 2 there are four adverts characteristic, namely: Public Presentation appears in 1 scene, Persuasiveness appears in 2 scenes, Amplified Expresiveness appears in 2 scenes, and Impersonality appears in 4 scenes. The product placement in this film appears that the Impersonality advertisement is very dominant, then followed by the Amplified Expresiveness and Persuasiveness advertisement. Meanwhile, advertising in a Public Presentation characteristic only appears in one scene.